Increasing the efficiency of the organization of marketing activity of coal enterprises - Zaloznova, Yu.; Trushkina, N. (Економічний вісник Донбасу, 2017)
Performance features of coal mining enterprises in terms of organization of the marketing activity were studied. The essence of the concept «marketing activity of coal-mining enterprise» is specified, taking into account the specifics of its performance and detected changes and development trends of the institutional environment. The author's interpretation of the terms «relation marketing», «customer orientation», «consumer service of the coal product», «sales network» are given. Network approach to organization of the marketing activity of coal mining enterprises is proposed, which main point is the development of three models of sales networks.
Based on the analysis of scope and pattern of coal consumption in Ukraine, common factors of irregular demand for coal of different categories of consumers are determined. As per calculations of seasonal fluctuations index it is estimated that demand for coal of large-scale consumers is characterized by weak seasonal fluctuations and of middle-scale – by significant. It is offered a customer-oriented approach to servicing consumers of coal products based on differentiation thereof, which unlike the existing one, considers annual demand level of different groups of consumers and determine their peculiarities.
It is established that in order to improve the processes of servicing of coal consumers it is reasonable to use in a single package the system, process and functional approaches. This shall contribute to synergistic effect through the improvement of service quality, reducing handling time of coal, increasing sales, expanding markets as a result of new segments upraise. The factors influencing the organization of sales of coal mining enterprises are investigated and systematized. The inertial and optimistic scenarios for the development of sales policy of coal-mining enterprises through the use of various forecasting methods are developed.
Selection criteria for optimal channel of coal product sale are specified and systematized into four groups: economic, organizational, market and information. Using hierarchy analysis technique (Saaty’s method), judgmental method based on point factor and analytical appraisal method the advantages of direct supply of coal to customers are proved, which amounts almost 90% of sales of coal mining enterprises. When calculating the volume of the delivery of coal products to large-scale consumers it is proposed to take into account such factors as annual demand for coal; price of 1 t of marketable product; expenses for the organization of sales (expenses for consumer service and transportation of coal); inflation rate and risk factor.
Mechanism of implementation of public-private partnership is improved during control over sales of coal mining enterprises of different forms of ownership based on syndicate as a form of business, what shall contribute to prompt response to changes in demand for coal, distribution of risks between coal enterprises of public and private sectors and their minimization, organization of continuous supply and secured channels of distribution of coal products for national coal-mining enterprises.
The system of contractual relationships of coal producers with various categories of coal consumers is built, which is understood as a set of interrelated elements (objects, subjects, functions, methods, principles, tools) for continuous conclusion and fulfillment of the terms of contracts for the delivery of coal products. The methodical approach is being further developed to evaluation of economic potential from implementation of measures on improvement of sales of coal mining enterprises, which has been tested on a number of national coal mining enterprises. Досліджено особливості функціонування вугледобувних підприємств з точки зору організації збутової діяльності. Уточнено суть і зміст понять «збутова діяльність вугледобувного підприємства», «маркетинг взаємовідносин», «клієнтоорієнтованість», «обслуговування споживачів вугільної продукції», «збутова мережа». Доведено доцільність застосування мережевого підходу до організації збутової діяльності вугледобувних підприємств.
У результаті аналізу обсягів і структури споживання вугілля в Україні виявлено закономірності нестабільності попиту на вугільну продукцію різних категорій споживачів. Запропоновано застосування клієнтоорієнтованого підходу до обслуговування споживачів вугільної продукції на основі їх диференціації, який, на відміну від існуючих, базується на врахуванні обсягів щорічного попиту різних груп споживачів та їх специфічних особливостей.
Встановлено, що для вдосконалення обслуговування споживачів вугільної продукції доцільним є поєднання системного, процесного і функціонального підходів. Досліджено та систематизовано чинники впливу на організацію збутової діяльності підприємств вугільної промисловості. Розроблено інерційний та оптимістичний сценарії розвитку збутової політики вугледобувних підприємств за допомогою різних методів прогнозування.
Удосконалено методичний підхід до вибору оптимального каналу збуту вугільної продукції з використанням методу аналізу ієрархій, експертного й аналітично-оціночного методів. Розроблено механізм реалізації державно-приватного партнерства при управлінні збутовою діяльністю вугледобувних підприємств різних форм власності у вигляді синдикату.
Сформовано систему контрактних взаємовідносин вугледобувного підприємства з різними категоріями споживачів вугільної продукції. Дістав подальшого розвитку методичний підхід до оцінки економічного ефекту від реалізації заходів щодо вдосконалення організації збутової діяльності вугледобувних підприємств, який апробовано на вітчизняних підприємствах вугільної промисловості. Исследованы особенности функционирования угледобывающих предприятий с точки зрения организации сбытовой деятельности. Уточнены сущность и содержание терминов «сбытовая деятельность угледобывающего предприятия», «маркетинг взаимоотношений», «клиентоориентированность», «обслуживание потребителей угольной продукции», «сбытовая сеть». Доказана целесообразность применения сетевого подхода к организации сбытовой деятельности угледобывающих предприятий.
В результате анализа объемов и структуры потребления угля в Украине выявлены закономерности нестабильности спроса на угольную продукцию различных категорий потребителей. Предложено применение клиентоориентированного подхода к обслуживанию потребителей угольной продукции на основе их дифференциации, который, в отличие от существующих, базируется на учете объемов ежегодного спроса различных групп потребителей и их специфических особенностей.
Установлено, что для совершенствования обслуживания потребителей угольной продукции целесообразно сочетание системного, процессного и функционального подходов. Исследованы и систематизированы факторы влияния на организацию сбытовой деятельности предприятий угольной промышленности. Разработаны инерционный и оптимистический сценарии развития сбытовой политики угледобывающих предприятий с помощью различных методов прогнозирования.
Усовершенствован методический подход к выбору оптимального канала сбыта угольной продукции с использованием метода анализа иерархий, экспертного и аналитико-оценочного методов. Разработан механизм реализации государственно-частного партнерства при управлении сбытовой деятельностью угледобывающих предприятий различных форм собственности на основе создания синдиката.
Сформирована система контрактных взаимоотношений угледобывающего предприятия с различными категориями потребителей угольной продукции. Получил дальнейшее развитие методический подход к оценке экономического эффекта от реализации мероприятий по совершенствованию организации сбытовой деятельности угледобывающих предприятий, который апробирован на отечественных предприятиях угольной промышленности.